Jovens trabalhadoras e o sofrimento ético-político - Dias, Maria Dionísia do Amaral [UNESP] (FapUNIFESP (SciELO), 2014)
The article analyzes the experience of young female workers, in the Social-historical Psychology perspective, based on a case study with workers, 17-24 years, of industries on city in the state of São Paulo, Brasil. Discusses how the politics of affectivity at work operates a blockage to liberty and to full development, conforming an ethical-political suffering which affects health, conceived as potency to action, thus characterizing work as a form of perverse inclusion. In a context in which the employment of young workers is considered as a social problem, the present research discusses another side of the question: the reality of young people who are already inserted in the labor market, associating their experience to issues such as health and formation to future, taking into account the importance of this stage of human development.

El artículo examina las experiencias de los trabajadores jóvenes desde la perspectiva de la psicología sociohistórico, basado en un estudio de caso con trabajadores, 17 a 24 años, de industrias de una ciudad en el estado de São Paulo. Discute cómo la política del afecto en el trabajo opera en el bloqueo de la libertad y el pleno desarrollo, lo que distancia los trabajadores jóvenes de su singularidad, que se ofrece como un sufrimiento ético-político que afecta a la salud, su poder de la acción, que caracteriza trabajar como una forma perversa de inclusión. En un contexto en el que se busca garantizar la inclusión de los jóvenes en el mercado laboral, se aborda otro lado de la cuestión, la realidad de los jóvenes que trabajan, relacionando esta experiencia a las cuestiones de salud y educación para su futuro, teniendo en cuenta la importancia de este etapa del desarrollo humano.

O artigo analisa a vivência de trabalhadores jovens, numa perspectiva da psicologia sócio-histórica, com base em estudo de caso com trabalhadoras, de 17 a 24 anos, de indústrias de confecção de uma cidade do interior paulista. Discute como a política de afetividade no trabalho opera no bloqueio à liberdade e ao pleno desenvolvimento, distanciando jovens trabalhadores de seus próprios afetos, da sua singularidade, configurando um sofrimento ético-político que afeta a saúde, concebida como potência de ação, o que caracteriza o trabalho como uma forma de inclusão perversa. Num contexto em que se busca garantir a inserção dos jovens no mercado de trabalho, o artigo discute outra face da questão, a realidade de jovens que trabalham, relacionando essa experiência às questões de saúde e formação para seu futuro, considerando-se a importância dessa fase do desenvolvimento humano.
Young female workers and the Ethical-Political suffering
Trabajadores Jóvenes y el sufrimento Ético-Político
Keywords: Worker’s health; Health of young; Ethical-political suffering; Mental health; Work; Salud en el trabajo; La salud de los jóvenes; Sufrimiento ético-político; Salud mental; Trabajo; Saúde do trabalhador; Saúde do jovem; Sofrimento ético-político; Saúde mental; Trabalho